L'allocation des ressources et leur niveau d'emploi dans le chapitre 21 de la Théorie Générale (2006)
ABSTRACT: The aim of this paper is to show the role of prices in Keynes’s monetary theory. More precisely, we show that in chapter 21 of the General Theory there exists a mechanism of relative prices. The employment level is determined, simultaneously, by effective demand and by relative prices. This result is derived from Keynesian price theory. In this theory, a rise in the quantity of money produces a non proportional price variation through effective demand. We show that Keynes’s theory is, at the same time, a theory of relative prices and a theory of the price level.